Bennet Woodcroft and the value of English patents, 1617-1841 - Alessandro Nuvolari; Valentina Tartari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
We examine the potentialities of a new indicator measuring the value of English patents in the period 1617-1841. The indicator is based on the relative visibility of each individual patent in the contemporary technical and legal literature as summarized in Bennet Woodcroft's Reference Index of Patents of Invention. We conclude that the indicator provides a reasonable proxy for the value of patents and that it can be usefully employed to shed light on the timing and scope of innovation during the Industrial Revolution. In particular, our indicator offers a suitable reconciliation between the patent records evidence and the Crafts-Harley view of the Industrial Revolution.
Keywords: 330